From Customary Law to State Law: Ancestral Property Disputes in Minangkabau through Islamic Law - Nabila Fitri Gunawan; Edi Rosman (Hakamain: Journal of Sharia and Law Studies, 2026)
This study aims to examine the transformation of ancestral property (harta pusaka) disputes in the Minangkabau matrilineal system from customary law (adat) into state law, with a particular focus on how Islamic law interprets, mediates, and influences such conflicts. The research seeks to analyze the tension between adat inheritance norms, which prioritize maternal lineage, and statutory legal frameworks that increasingly regulate property disputes within Indonesia’s national legal system. The methodology employed is qualitative juridical research with a normative-empirical approach. Primary legal materials include Islamic legal texts (Qur’an, Hadith, and classical fiqh), Indonesian inheritance law regulations, and customary law principles of Minangkabau society. Secondary data are derived from scholarly literature, case studies, and relevant court decisions. Data analysis is conducted through comparative legal analysis and interpretative content analysis to identify intersections and divergences among adat, state law, and Islamic legal principles. The findings indicate that ancestral property disputes in Minangkabau arise from dual legal legitimacy between adat inheritance (collective matrilineal ownership) and Islamic inheritance law (individual bilateral distribution). State law functions as an intermediary but often fails to fully reconcile these normative systems, leading to prolonged disputes. Islamic law, particularly through the principles of maslahah (public interest) and ‘urf (custom), provides a flexible framework for harmonizing customary practices with normative Islamic injunctions. The study concludes that a hybrid legal approach is essential to resolve inheritance conflicts in Minangkabau, integrating adat legitimacy with Islamic legal ethics and national legal certainty. The academic contribution of this research lies in offering a comparative synthesis model that bridges customary matrilineal inheritance and Islamic legal theory, contributing to broader discourse on legal pluralism and family law reform in Indonesia.